The Effects of International Accounting Standards (IAS) - International Financial Reporting Standards (IFRS) Application to an Entity’s Assets - BOGDAN, Anca Mădălina (Journal of Advanced Research in Management, 2020)
The qualitative research of this study was based on the study of the content of the OMFP provisions and the analysis of the content of the IFRS conceptual framework. The analysis presents the statements regarding the general accounting principles of OMFP 1802/2014 and the IFRS reference. We have researched numerous specialized studies on the application of financial reporting principles, how the process affects decision-making when principles-based standards are applied, and the influence of the principle on rules-based standards. Finally, we practically demonstrated the need for restatements and accounting changes in order to accurately present the position and financial results of the studied entity.